Transcriptome Analysis of Cordyceps militaris Reveals Genes Associated With Carotenoid Synthesis and Identification of the Function of the Cmtns Gene - Lou, Hai-Wei; Zhao, Yu; Tang, Hong-Biao; Ye, Zhi-Wei; Wei, Tao; Lin, Jun-Fang; Guo, Li-Qiong (Frontiers in Microbiology, 2019)
Cordyceps militaris, a valuable edible and medicinal fungus, has attracted increasing attention because of its various bioactive ingredients. However, the biosynthetic pathway of C. militaris carotenoids is still unknown due to lack of transcriptome information. To uncover genes related to the biosynthesis of C. militaris carotenoids, the transcriptomes of mycelia CM10_D cultured under dark conditions and mycelia CM10_L cultured under light exposure conditions were sequenced. Compared with mycelia CM10_D, 866 up-regulated genes and 856 down-regulated genes were found in mycelia CM10_L. Gene Ontology (GO) analysis of differentially expressed genes (DEGs) indicated that DEGs were mainly classified into the "metabolic process", "membrane", and "catalytic activity" terms. KEGG pathway enrichment analysis of DEGs suggested that DEGs were mainly enriched in “metabolic pathways”, “MAPK signaling pathway-yeast”, and “biosynthesis of secondary metabolites”. In addition, the carotenoid content of the Cmtns gene deletion mutant (ΔCmtns) was significantly lower than that of the wild-type C. militaris CM10, while the carotenoid content of the complementary strain (ΔCmtns-c) of the Cmtns gene was not significantly different from that of C. militaris CM10, suggesting that the Cmtns gene significantly affected the biosynthesis of carotenoids in C. militaris. These results potentially pave the way for revealing the biosynthetic pathway of carotenoids and improving carotenoids production in C. militaris.